Quantitative sodium magnetic resonance imaging of cartilage, muscle, and tendon - Bangerter, Neal K. (Quant Imaging Med Surg, 2016)
Sodium magnetic resonance imaging (MRI), or imaging of the 23Na nucleus, has been under exploration for several decades, and holds promise for potentially revealing additional biochemical information about the health of tissues that cannot currently be obtained from conventional hydrogen (or proton) MRI. This additional information could serve as an important complement to conventional MRI for many applications. However, despite these exciting possibilities, sodium MRI is not yet used routinely in clinical practice, and will likely remain strictly in the domain of exploratory research for the coming decade. This paper begins with a technical overview of sodium MRI, including the nuclear magnetic resonance (NMR) signal characteristics of the sodium nucleus, the challenges associated with sodium MRI, and the specialized pulse sequences, hardware, and reconstruction techniques required. Various applications of sodium MRI for quantitative analysis of the musculoskeletal system are then reviewed, including the non-invasive assessment of cartilage degeneration in vivo, imaging of tendinopathy, applications in the assessment of various muscular pathologies, and assessment of muscle response to exercise.